Roles of Non-Coding RNA in Anthracycline Cardiotoxicity: A Narrative Review - Xiao S; Li Y; Li B; Wang H; Wang K; Yang S (Journal of Inflammation Research)
Shudan Xiao,* Yinghui Li,* Bo Li,* Haoxuan Wang, Kun Wang, SuMin Yang Department of Cardiovascular Surgery, The Affiliated Hospital of Qingdao University, Institute of Chronic Diseases, College of Medicine, Qingdao University, Qingdao, People’s Republic of China*These authors contributed equally to this workCorrespondence: Kun Wang; SuMin Yang, Email wangk696@qdu.edu.cn; SMinYangFY@126.comAbstract: Anthracyclines, renowned for their efficacy and widespread application as antitumor agents, have substantially contributed to the enhancement of cancer patients’ survival rates. Nonetheless, anthracyclines predominantly account for the cardiotoxic effects, both acute and chronic, experienced by individuals undergoing cancer treatment. Anthracycline-induced cardiotoxicity (AIC) usually leads to progressive systolic dysfunction of the left ventricle, which may subsequently develop into heart failure and even death. Therefore, more stable, specific and sensitive auxiliary diagnostic biomarkers are needed. Non-coding RNAs, comprising long non-coding RNAs (lncRNAs), microRNAs (miRNAs), and circular RNAs (circRNAs), are pivotal in regulating cardiac metabolism, apoptosis, and oxidative stress, emerging as key targets for cardiovascular disease prevention and treatment. This review encapsulates the recent advancements in the field of non-coding RNA research in AIC, highlighting the prospect of non-coding RNAs as potential biomarkers and therapeutic targets for the condition. These molecules are known to regulate key cardiac processes including metabolism, apoptosis, and oxidative stress, which are central to the pathology of AIC. The potential of these molecules as diagnostic and prognostic indicators is significant, with miRNAs, for instance, being studied for their role in resistance to chemotherapeutic drugs and their application in therapeutic strategies. The review underscores the importance of understanding the intricate mechanisms by which non-coding RNAs influence gene expression and contribute to the development and progression of AIC, offering new avenues for targeted therapies and personalized treatment plans.Keywords: anthracycline-induced cardiotoxicity, non-coding RNA, oxidative stress, apoptosis